An Exploration of the Forward Premium Puzzle in Currency Markets - Bansal, Ravi (Review of Financial Studies, 1997)
A standard empirical finding is that expected changes in exchange rates and interest rate differentials across countries are negatively related, implying that uncovered interest rate parity is violated in the data. This article provides new empirical evidence that suggests that violations of uncovered interest rate parity, and its economic implications, depend on the sign of the interest rate differential. A framework related to term structure models is developed to account for the puzzling relationship between expected changes in exchange rates and interest rate differentials. Estimation results suggest that a particular term structure model can account for the puzzling empirical evidence.